PENGARUH PROMOSI SOSIAL MEDIA DAN WORD OF MOUTH TERHADAP KEPUTUSAN PEMBELIAN DI LIPPO MALL KARAWACI TANGERANG - Widyanti, Dika Vivi; Azizah, Azizah (Politeknik Negeri Semarang, 2023)
Technological development is progressing today, many social media users in Indonesia are very wise in using smartphone devices to open up very easy business opportunities. The presence of digital marketing can help sell a product, because the internet allows the marketing process to be more effective, efficient and customer feedback faster and does not require high costs. As for reading how to promote a product, that is, through social media and with words. Word of mouth is one of the most efficient and effective marketing techniques in which consumers can exchange information about the product or goods to be marketed so that it can influence consumers to buy the product. Certainly with the presence of the influence or impact of social media in the product marketing process becomes one of the most current marketing strategies and very fast customer feedback makes business actors use this strategy to improve insight or sales of the business they do. As for the positive collaboration between the influence of social media and words, it is capable to attract consumers in making purchasing decisives. The study used a quantitative descriptive method approach, the researchers wanted to prove that consumers were paying attention to promotions through social media conducted by Lippo Mall Karawaci. With the influence of Word of Mouth, client get alternative judgments in determining product purchase decisions. The information obtained is simple and interesting and followed by a positive delivery of other people”™s experiences in purchasing the product, it will be very easy to improve the buyer”™s decision at the Lippo Mall Karawaci.